Larval description of Theloderma albopunctatum (Liu & Hu, 1962) (Anura: Rhacophoridae) from Northern Vietnam, with comparison between the North-Vietnamese and North-eastern Thai clades - Ginal, Philipp; Schmitz, Lisa M.; Rödder, Dennis (Zootaxa, 2022)
The mossy frogs of the genus Theloderma Tschudi comprise 28 described taxa (Sivongxay et al. 2016; Frost 2022), which are distributed from north-eastern India and Myanmar to southern China, across the peninsula of Indochina and Malaysia, to Indonesia (Poyarkov et al. 2015; Frost 2022). Theloderma albopunctatum is a small-sized taxon that is assigned to the T.-asperum species complex (Poyarkov et al. 2015, 2018; Sivongxay et al. 2016; Dever 2018). For long time, it has been believed to be a synonym of T. asperum. However, genetic analyses revealed that both taxa show significant differences. Currently, populations south of the Isthmus of Kra (southern Thailand, Malayan peninsular) are assigned to T. asperum, while populations north of it (southern China, northern and central Vietnam, adjacent Laos, south-eastern Cambodia) are assigned to T. albopunctatum. In addition, this species complex might contain further cryptic species (cf. Nguyen et al. 2015; Poyarkov et al. 2015) and according to Chunskul et al. (2021) four genetic groups do exist: group A comprises T. albopunctatum from southern and central Vietnam, Laos, central and north-eastern Thailand; group B is composed of populations from northern Vietnam and China; group C ranges from north-western Vietnam to northern Thailand and Myanmar; and group D is distributed in northern Vietnam (Thanh Hoa).